Social Capital and growth in the European Regions - Isabel Neira; Marta Portela; Elvira Pacheco Vieira (European Regional Science Association (ERSA), 2010)
Theories of economic growth at the regional and national level, have expanded the traditional production function of the Solow model towards a wide function that collects conditioning factors of labour productivity, measured by R & D expenditure, the number of patents, the human capital, the social capital or entrepreneurship rates. This set of factors have been developed by authors like Westlund (2006) and Koo and Kim (2009). The aim of this paper is to analyze regional growth in the EU, considering the differences between the EU15 and its eastern regions, using such set of factors and taking into account the limitations of existing data for this type of analysis.
Keywords: 330